The lean practitioner's field book : proven, practical, profitable and powerful techniques for making lean really work /: proven, practical, profitable and powerful techniques for making lean really work. (2015) - Protzman, Charles; Whiton, Fred; Kerpchar, Joyce; Lewandowski, Christopher; Stenberg, Steve; Grounds, Patrick
No abstract available